Dampak Penurunan Hambatan dan Peningkatan Kemudahan Perdagangan Terhadap Produksi, Neraca Perdagangan Pertanian, dan Kesejahteraan Masyarakat - Budiman F. Hutabarat (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2015)
EnglishIn tandem with the effort of WTO that insists its members to cut their tariff, standardization, and in general, the non-tariff measures/NTMs have been gaining its role in today’s world agricultural and food trade. The objectives of this paper is to review information and data pertaining to NTM and trade facilitation imposed by Indonesia’s partner countries and investigate their impact on agricultural production and welfare. Based on GTAP Data Base Version 8.1, the paper concludes that Vegyfru (Vegetables, fruit, nuts) and Vegyoil (Vegetable oils and fats) production tend to increase, but for those of Oilseed, Othfoodpr (Food products nec) and Oth_sectors (Other sectors), some scenarios project to their increases and other scenarios show otherwise. Inspite of that all scenarios results in positive increases in welfare of Indonesians and world’s population between US 16 to 1,734 million. For Indonesia, improvement in trade facilitation in all regions would give the most benefits, relative to import tariff reduction done by partner countries or export tax/subsidy reduction done by all regions, including Indonesia. The paper suggests that Indonesia should actively follow the policy dynamics that relate to NTMs and trade facilitation applied by the partner countries on agricultural products’ tariff lines in terms of types, size, and its characteristics. By so doing, Indonesia would gain a deeper understanding on defensive and offensive trade and economic interests of each of its partner countries and its own. IndonesianSeiring dengan pemotongan tarif secara menyeluruh di seluruh dunia yang digalakkan Organisasi Perdagangan Dunia (OPD), pembakuan, dan secara umum tindakan bukan-tarif/TBT atau non-tariff measures/NTMs, menjadi makin penting perannya dalam perdagangan pertanian dan pangan dunia saat ini. Tujuan makalah ini adalah mendapatkan informasi dan data tentang hambatan perdagangan bukan-tarif dan kemudahan perdagangan yang diterapkan negara-negara mitra dan dampaknya pada produksi pertanian dan kesejahteraan masyarakat Indonesia. Hasil analisis dengan menggunakan Basis Data GTAP Versi 8.1 menunjukkan bahwa produksi Vegyfru (Vegetables, fruit, nuts) dan (Vegetable oils and fats), dan untuk Oilseed, Othfoodpr (Food products nec) dan Oth_sectors (Other sectors) beberapa skenario menunjukkan peningkatan, tetapi beberapa lainnya menunjukkan penurunan. Semua skenario yang dipertimbangkan memberi peningkatan kesejahteraan bagi Indonesia dan dunia, antara US 16 sampai US 1.734 juta dolar AS. Bagi Indonesia kebijakan peningkatan keefisienan perdagangan di seluruh dunia memberikan manfaat yang paling besar dibandingkan dengan kebijakan pemotongan tarif impor atau pemotongan tarif ekspor. Saran kebijakan yang dapat disampaikan antara lain Indonesia perlu secara aktif mengikuti perkembangan kebijakan yang menyangkut tindakan bukan tarif/TBT dari sisi jenis, besaran, dan sifatnya untuk setiap pos tarif komoditas pertanian yang lebih rinci yang dilakukan negara-negara mitra. Dengan demikian, pengetahuan yang mendalam tentang daya bertahan dan daya serang perdagangan suatu negara mitra dan Indonesia sendiri dapat diperoleh.